Current and future outlook of loaded components in hydrogel composites for the treatment of chronic diabetic ulcers - Cui, Jiaming; Zhang, Siqi; Cheng, Songmiao; Shen, Hai (Frontiers in Bioengineering and Biotechnology, 2023)
Due to recalcitrant microangiopathy and chronic infection, traditional treatments have difficulty producing satisfactory results for chronic diabetic ulcers. In recent years, due to the advantages of high biocompatibility and modifiability, an increasing number of hydrogel materials have been applied to the treatment of chronic wounds in diabetic patients, among which the research of composite hydrogels has received increasing attention since different loaded components greatly increase the ability of composite hydrogels to treat chronic diabetic wounds. This review summarizes and discusses in detail a variety of types of newly loaded components currently used in hydrogel composites in the treatment of chronic diabetic ulcers, such as polymer/polysaccharides/organic chemicals, stem cells/exosomes/progenitor cells, chelating agents/metal ions, plant extracts, proteins (cytokines/peptides/enzymes) and nucleoside products, and medicine/drugs. hoping to help researchers understand the characteristics of these components in the treatment of diabetic chronic wounds This review also discusses a number of components that have not yet been applied and have the potential to be loaded into hydrogels, all of which play a role in the biomedical field and may become important loading components in the future. This review provides a "loading component shelf" for researchers of composite hydrogels and a theoretical basis for the future construction of "all-in-one" hydrogels.